Assessment on the Effectiveness of Romanian Bicameralism During the 2004-2005 Term - Cynthia Carmen CURT (Transylvanian Review of Administrative Sciences, 2006)
The present study proposes an analysis of bicameralism, marking the 2000-2005 term on account of the legislative stability and direct intervention of the bicameral Parliament in the fields subject to law making. The analysis attempts to observe the means by which the Senate is able to accomplish its role of Chamber of reflection, and implicitly that of factor of stability in the Romanian bicameral law-enacting process.